A novel Adolescent Health Behavior Checklist - Su, Yanjie; Bai, Hua; Li, Ying; Zhang, Yang (Frontiers in Public Health, 2025)
PurposeAdolescents are experiencing rising rates of obesity, insufficient exercise, and sleep disorders. To provide a scientific basis for policymakers to develop targeted and evidence-based health behavior education and policies, this study employed structural equation modeling to design the Adolescent Health Behavior Checklist (AHBC).MethodsWe designed a draft 6-dimensional AHBC, which includes the dimensions of exercise, diet, personal responsibility, sleep, interpersonal relationships, and stress management. Each item is rated on a 5-point Likert scale, with higher scores indicating healthier behavior. Through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), we optimized the construct validity of the AHBC.ResultsThe optimal factor structure was first determined using EFA with 177 middle school students participating in the process. EFA suggested a hierarchical, 6-factor AHBC with good internal consistency (global Cronbach's alpha = 0.96). Using an independent sample of 349 middle school students, CFA confirmed the construct validity of the AHBC. The final model demonstrated a good fit: SRMR = 0.058, CFI = 0.990. Five out of six latent variables had factor loadings higher than 0.7, and 81% of the item-level factor loadings exceeded 0.7. Additionally, all latent variables had McDonald's omega values higher than 0.7, indicating acceptable convergent validity. Finally, factor correlations showed that the AHBC has good discriminant validity.ConclusionsThe AHBC is a 31-item checklist that assesses adolescents' all-around health behaviors, using a score of four as the benchmark value. The shortcomings of the current checklist are discussed, along with future theoretical and practical directions for improvement.